POSSIBILITIES OF USING MODERN TECHNOLOGIES IN SOLVING PROBLEMS IN MECHANICS BASED ON MODELING (American Journal of Pedagogical and Educational Research, 2026)
This article examines the role and importance of artificial intelligence technologies in solving mechanics problems using modeling methods. Modern approaches problems using machine learning, neural networks, and computer simulation are analyzed. The formation of practical skills among students the integration of artificial intelligence into the educational process, as well as the modeling of complex dynamic systems, are discussed. The research results demonstrate the positive impact of artificial intelligence on mechanics education.